Polyandry, Predation, and the Evolution of Frog Reproductive Modes - Zamudio, Kelly R.; Bell, Rayna C.; Nali, Renato C. [UNESP]; Haddad, Celio F. B. [UNESP]; Prado, Cynthia P. A. [UNESP] (Univ Chicago Press, 2016)
Frog reproductive modes are complex phenotypes that include egg/clutch characteristics, oviposition site, larval development, and sometimes, parental care. Two evident patterns in the evolution of these traits are the higher diversity of reproductive modes in the tropics and the apparent progression from aquatic to terrestrial reproduction, often attributed to higher fitness resulting from decreased predation on terrestrial eggs and tadpoles. Here, we propose that sexual selection-and not only natural selection due to predation-favors terrestrial breeding by reducing the loss of fitness due to polyandry. To examine this novel selective mechanism, we reconstructed the evolution of reproductive diversity in two frog families (Hylidae and Leptodactylidae) and tested for concerted evolution of egg and tadpole development sites with specific mating behaviors. We found that oviposition and tadpole development sites are evolving independently, do not show the same diversity and/or directionality in terms of terrestriality, and thus may be diversifying due to different selective mechanisms. In both families, terrestrial egg deposition is correlated with amplexus that is hidden from competing males, and in hylids, testes mass was significantly larger and more variable in males with exposed amplexus that are vulnerable to polyandry. Our results indicate that intrasexual selection has been an underappreciated mechanism promoting diversification of frog reproductive modes.
Keywords: Anura; phylogenetic comparative methods; reproduction; sexual selection; multimale spawning